2012
DOI: 10.1371/journal.pone.0031052
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Drives Cellular Senescence

Abstract: The accepted androgen receptor (AR) role is to promote proliferation and survival of prostate epithelium and thus prostate cancer progression. While growth-inhibitory, tumor-suppressive AR effects have also been documented, the underlying mechanisms are poorly understood. Here, we for the first time link AR anti-cancer action with cell senescence in vitro and in vivo. First, AR-driven senescence was p53-independent. Instead, AR induced p21, which subsequently reduced ΔN isoform of p63. Second, AR activation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 66 publications
(87 reference statements)
9
49
0
Order By: Relevance
“…The induction of cellular senescence has been described for PC3 cells, a human metastatic PCa cell line that have originally lost AR expression, stably transfected with the human AR and treated with the androgen R1881, defined there as DHT [47]. We confirmed also the androgen-induced cellular senescence in PC3-AR cells.…”
Section: Discussionsupporting
confidence: 78%
“…The induction of cellular senescence has been described for PC3 cells, a human metastatic PCa cell line that have originally lost AR expression, stably transfected with the human AR and treated with the androgen R1881, defined there as DHT [47]. We confirmed also the androgen-induced cellular senescence in PC3-AR cells.…”
Section: Discussionsupporting
confidence: 78%
“…5A) support that several key changes such as elevated Mcl-1 expression appear to be senescence- rather than AR-dependent. Indeed, AR expression has a complex relationship with senescence induction in prostate cancer cells, with a recent report showing that constitutive AR overexpression can also induce senescence, albeit via a p21-dependent rather than p16-dependent mechanism [86].…”
Section: Discussionmentioning
confidence: 99%
“…A recent application of the same Rbpj-knockout mouse as utilised by Buono et al (2006) has suggested that the basal MECs expansion observed during pregnancy in these mice was due to MECs deficient in NOTCH signalling being outcompeted by WT MECs, supporting the idea that NOTCH signalling is critical for basal bipotent progenitor MECs to take on a luminal fate through suppression of P63 (Yalcin-Ozuysal et al 2010). A role for AR in antagnoising the effects of P63, via the cell cylcle regulator P21, has been identified in prostate epithelium (Mirochnik et al 2012), and it possible that a similar mechanism is at play in the mammary epithelium.…”
Section: Inducible Expression Of Notch1 In All Mecsmentioning
confidence: 92%